Influences of DRA and non-DRA vision on visual responses of locusts stimulated by linearly polarized and unpolarized lights - Zou, Shengguang; Liu, Tao; Ma, Yicheng; Zhang, Pingchuan; Liu, Qihang (International Journal of Agricultural and Biological Engineering, 2023)
Locust and grasshopper plagues pose a serious threat to crop production in many areas worldwide. However, there is a lack of effective, quick-acting methods to control such outbreaks. Methods exploiting the phototactic response of these insects are receiving increasing attention. The current study investigated the effect of linearly polarized and unpolarized light on locust phototactic and polarotactic responses, in particular the function of their dorsal rim area (DRA) and non-DRA visual fields. The results showed that the polarotactic function weight of DRA vision was stimulated by linearly polarized ultraviolet (UV) and violet light, the phototactic function weight was induced by blue, green, and orange light, and under linearly polarized light, the functional effect of DRA vision was strongest in response to linearly polarized violet light. Moreover, the locust visual response effect was related to spectral light attributes, with the linear polarization effect intensifying in response to the short-range vision sensitivity of non-DRA visual fields, whereas DRA vision regulated the short-range sensitivity of compound eye vision. When illumination increased, the synergistic enhancement effects of linearly polarized ultraviolet and violet light were significant, whereas the visual sensitivity was restricted significantly by linearly polarized blue, green, or orange light. Thus, non-DRA vision determined, while DRA vision enhanced, the phototactic response sensitivity, whereas, in linearly polarized UV or violet light, non-DRA vision determined, while DRA vision enhanced, the visual trend and polarotaxic aggregation sensitivity, with opposite effects in linearly polarized blue, green, or orange light. When illumination increased, there was a driving effect caused by linearly polarized violet light on non-DRA vision, whereas at short-wave lengths, the control effect induced by linearly polarized orange light was optimal; however, the photo-induced effect of linearly polarized violet light and the visual distance control effect of linearly polarized orange light were optimal. These results provide theoretical support for the photo-induced mechanism of the locust visual response effect and for the development of linearly polarized light sources for the environmentally friendly prevention and control of locust populations.Keywords: Locusta migratoria, linearly polarized light, spectral light, visual response, DRA and non-DRA visionDOI: 10.25165/j.ijabe.20231603.7959Citation: Zou S G, Liu T, Ma Y C, Zhang P C Liu Q H. Influences of DRA and non-DRA vision on visual responses of locusts stimulated by linearly polarized and unpolarized lights. Int J Agric & Biol Eng, 2023; 16(3): 15–22.